Impact of genotype and harvest age on the polyphenol content and antioxidant capacity of okra (Abelmoschus esculentus) in Indonesia - NOVIAN LIWANDA; MUHAMAD SYUKUR; WARAS NURCHOLIS (Society for Indonesian Biodiversity, 2024)
Abstract. Liwanda N, Syukur M, Nurcholis W. 2024. Impact of genotype and harvest age on the polyphenol content and antioxidant capacity of okra (Abelmoschus esculentus) in Indonesia. Biodiversitas 25: 4920-4929. Consuming bioactive compounds like polyphenols and flavonoids is crucial for reducing the risk of diseases due to their antioxidant, antibacterial, and anticancer properties. Okra (Abelmoschus esculentus), a widely cultivated vegetable known for its nutritional benefits, remains underutilized in Indonesia. This study aimed to identify the optimal genotype and harvest age of okra to maximize total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity. Ten okra genotypes were evaluated, with a focus on the impact of harvest age on four selected genotypes. The G7 genotype (F7 Clemson × Stripe-3-10-15B) exhibited the highest TPC (0.98 mg gallic acid equivalent/g fresh weight), TFC (0.35 mg quercetin equivalent/g fresh weight), and antioxidant capacity (5.13 µmol Trolox equivalent/g fresh weight). The optimal harvest age was determined to be the 7th day after anthesis, yielding the highest TPC and TFC values, ranging from 0.31 to 0.98 mg GAE/g and 0.19 to 0.35 mg QE/g, respectively. These findings indicate that both genotype and harvest age significantly affect the polyphenol content and antioxidant capacity of okra, with the G7 genotype and the 7th day after anthesis being optimal for maximizing bioactive compounds. This study highlights the potential for developing superior okra varieties in Indonesia.